Respon Limfosit T Sitotoksik Pada Gingivitis Setelah Pemberian Kurkumin (Citotoxic T Lymphocytes Response in Gingivitis After Curcumin Given) - Nitawati Meilisa Ni Putu; Dwi Merry Christmarini Robin; Mei Syafriadi (Pustaka Kesehatan, 2014)
Gingivitis is a form of periodontal disease most common in the community. Gingivitis is caused by bacteria in subgingival plaque, one of them is Porphyromonas gingivalis. Curcumin is a phenolic yellow pigment obtained from the powdered rhizome of Curcuma sp. which has anti-inflammatory effects. Curcumin can reduce the number and responses of cytotoxic T lymphocyte by signing on IL-1, IL-2, IL-12, and TNF. Variables observed in this study is the number and response of cytotoxic T lymphocyte in male Wistar rats gingiva. 16 male Wistar rats were divided into two groups: control and treatment groups. To cause gingivitis rats were injected with bacteria P. gingivalis 3x108 CFU concentrations as much as 0.02 ml of the gingival sulcus maxillary left for 2 days. The control group was given PBS and treatment group was given curcumin dose of 0.03 mg / g BW in intragastric starting from day 2 after induction of P. gingivalis. Rats sacrificed on day 3 (72 hours after the induction of P. gingivalis) and day 5, followed by extraction, fixation, tissue processing to be preparations with HE staining and IHC. Observation of the results carried out using a light microscope. Results showed that there was no cytotoxic T lymphocytes in the control and treatment groups, but in HE staining found existence of lymphocytes guess is that memory T lymphocytes (CD45). The conclusion of this study is in IHC staining method there is no difference in the number of cytotoxic T lymphocytes in the control group and the treatment, but in HE staining found existence of lymphocytes guess is that memory T lymphocytes, and the clinical features are redness and swelling until day 3 which the gingival more redness in the control group compared to the treatment group and healing has occurred on day 4 to day 5 in the control and treatment groups. Keywords: Citotoxic T lymphocytes, Curcumin, Gingivitis, Immunohistochemica